2014
DOI: 10.4149/bll_2014_097
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation in kidney and testis tissues in experimental hypothyroidism: the role of zinc

Abstract: Abstract:The aim of the present study was to determine the effect of zinc supplementation and zinc defi ciency on the lipid peroxidation in the testis and kidney tissues of rats with experimentally induced hypothyroidism. The experimental Groups were formed as follows: 1 -Control; 2 -Sham-Hypothyroidism; 3 -Hypothyroidism (intraperitoneal administration of 10 mg/kg/day PTU for 4 weeks); 4 -Hypothyroidism + 3 mg/kg/day zinc supplementation (4 weeks); 5 -Hypothyroidism + zinc defi ciency (4 weeks). The examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Ates et al (2016) have shown that serum total thiol levels were lower in patients with Hashimoto's thyroiditis than in healthy controls. In accordance with our results, previous studies have shown increased MDA levels in the heart (Messarah et al 2011), testis and kidney, and decreased GSH level in the testis and kidney in animal models of hypothyroidism (Baltaci et al 2013).…”
Section: Discussionsupporting
confidence: 94%
“…Ates et al (2016) have shown that serum total thiol levels were lower in patients with Hashimoto's thyroiditis than in healthy controls. In accordance with our results, previous studies have shown increased MDA levels in the heart (Messarah et al 2011), testis and kidney, and decreased GSH level in the testis and kidney in animal models of hypothyroidism (Baltaci et al 2013).…”
Section: Discussionsupporting
confidence: 94%
“…Th ese fi ndings are consistent with our previous study, which has shown hypothyroidism induced lipid peroxidation in the brain tissues Farrokhi et al 2014). Th e fi ndings of another study have demonstrated that in hypothyroidism, the MDA level was increased and GSH levels decreased in kidney tissues (Baltaci et al 2014). On the other hand, it has been well documented that thyroid hormones may infl uence the function of all body organs and cells.…”
Section: Discussionmentioning
confidence: 96%
“…Different defensive mechanisms that protect against the free radical damage have been characterized in various cellular localizations, including the endoplasmic reticulum, mitochondria, plasma membrane, peroxisomes and cytosol Littarru et al (1994). Enzymes such as GSH, GPx, ATPase and transition-metal binding proteins, such as transferrin, ferritin (that considered as iron carrier), prevent the production of inactivate free radicals, so GPx activity and other antioxidants as GSH decreased during hypothyroidism as antioxidants and also accompanied with hemoglobin deficiency as a result to ferritin depletion Baltaci et al (2014) these results are matches with the present study that show an increase in the level of livers' and kidneys' MDA and NO; this could be due to hypothyroidism-induced oxidative stress and a decrease level of GPx, ATPase and GSH and hemoglobin (ferritin) as antioxidants or free radical scavenging agents when compared with control group. It was reported that serum level of ASAT and ALAT were markedly increased in hypothyroidism Umezu et al (2016).…”
Section: Discussionmentioning
confidence: 99%